Pengaruh Corporate Governance Terhadap Environmental, Social, And Governance (esg) Sustainalytics Score: Studi Kasus Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Yang Telah Dilakukan Penilaian Oleh Sustainalytics Periode 2023 - Wulandari, Givanny Yusti; Wardoyo, Dwi Urip; Saraswati, Sri (eProceedings of Management, 2024)
This research focuses on ESG scores as measured by Sustainalytics in collaboration with the Indonesia StockExchange since 2023. It is unique because it examines the factors influencing the ESG scores of companies assessedby Sustainalytics. This study aims to examine the effects of board diligence, board gender diversity, and board size,along with the control variables of age and firm size, on ESG scores. The population of this study consists of 79companies assessed by Sustainalytics, with a sample of 78 observations selected using purposive sampling. Theanalysis was performed using descriptive statistics and cross-sectional multiple regression with Eviews version 12.This study found that board member diligence, board gender diversity, and board size simultaneously affect ESGscore, with controls for age and firm size. However, board gender diversity has a negative and significant effect onESG score, while board member diligence and board size do not have a significant effect. The results suggest thatfuture research should explore additional variables, such as financial ratios and green investments. For companies, these findings can serve as a basis for improving governance factors that impact ESG score. For investors, ESGscores assessed by independent institutions can be a crucial factor in making investment decisions. Keywords-board diligence, board gender diversity, board size, ESG.